Three New Species of the Genus Hypnoidus (Coleoptera, Elateridae) from Tibet - Dolin, W.G. (Вестник зоологии, 1999)
Three species of the genus Hypnoidus Dillwyn, 1829 are described as new: Hypnoidus patoni sp. n. similar to H. tibetanus Dolin & Cate, 1998, distinguishing by the double pronotum lateral margin, difFerent shape of the scutellum and flat intervals on elythra; H. alpinus sp. n. similar to H. himalayensis Stibick, 1978, distinguishing by the shape of pronotum, antennal segments and aedoeagus; H. beneschi sp. n., differing from all other species by its propleural punctuation and body shape. Type material is deposited mainly in the collection of Dr. P. C. Cate (Wien) and in the collection of the Schmalhausen Institut of Zoology (Kiev). Описываются три новых вида рода Hypnoidus Dillwyn,, 1829: Hypnoidus patoni sp. n., близкий к H. tibetanus Dolin & Cate,1998, отличается от последнего сдвоенным боковым краем переднегрудного сегмента, иной формой щитика и плоскими промежутками надкрылий; H. alpinus sp. n. напоминающий H. himalayensis Stibick, 1978, но хорошо отличающийся от него по форме переднегрудного сегмента, формой члеников усиков и строением гениталий; H. beneschi sp. n., отличающийся от всех известных из Центральной Азии видов грубой одинарной пунктировкой проплевр, полной редукцией боковых бороздок надкрылий и сильно выпуклым телом.